Búzalisztek minőségének becslése tészta nyújtás-szakítás alapján állományvizsgáló műszerrel - Horváthné Almássy, Katalin; Ács, Péterné; Baráné Herczegh, Ottilia; Deák, Anita (Acta Agraria Debreceniensis, 2002)
Literature experience was utilised to develop a method for the extensograph analog testing of paste with a QTS25 Texture Analyser. 54 wheat flour samples from the same variety from variety-preservation experiments at the Szeged were tested with this method. A study was made to establish whether the method is suitable for the estimation of results derived by traditional classification (trial baking, farinograph and gluten tests).A close and significant correlation was found between the hardness and area data measured with a QTS25 micro-extensograph, the farinograph values and the gluten spreading data, and also between the stretching index (BC/AC) and the water uptake capacity. These correlations correspond well with the findings from a previous experimental series on industrial flour samples. A close and significant correlation was likewise observed between the grain hardness established by the MININFRA method and all the QTS25 micro-extensograph data. In contrast with earlier QTS25 data, however a close correlation was not found between the QTS25 data and the loaf characteristics.With the use of micro-extensograph data, the estimation of the baking industry value has been improved through stepwise variable selection, with the inclusion of several variables. The estimation of loaf volume could also be solved by means of stepwise variable selection with the inclusion of QTS25 and MININFRA data.